IMPROVING SKILLS TO SCHOOL CHILDREN USING PUBLIC TRANSPORT IN SLOW LEARNER THROUGH METHOD OF EXERCISE (DRILL) - Imelia Sepriani (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract : The background of this study of the problems that researchers have found in a slow learner child class IX in SMP Negeri 34 Padang, which has not been able to in the skills to school using public transportation . Based on the case , this research aims to remedy proves that the method of exercise (drill ) can improve the skills to school using public transportation children slow learner X in SMP Negeri 34 Padang . This research is experimental research in the form of Single Subject Research ( SSR ) using ABA design and data analysis techniques using graphic visual analysis . The subjects were children slow learner . Results of the study appear ability skills to school using public transport on children slow learner can be increased by the method of training (drill ) . In the baseline condition ( A1 ), the percentage of children's ability lies in the range of 10 % -30 % . In the intervention condition ( B ) by using the method of exercise ( drill ) observations made ​​during the ten times of observation , the percentage of children ability lies in the range of 30 % -100 % . Later in the baseline condition ( A2 ) is performed five times of observation , the percentage of the school 's ability to use the skills of public transport lies in the range of 70 % -90 % . Based on these results it can be concluded that the method of training (drill ) can improve the skills of the child to school using public transportation on the slow learner in SMP Negeri 34 Padang . Suggested teachers want to provide a method of exercise ( drill ) to improve skills in children can be a slow learner so that an independent human being . Kata Kunci : Slow learner, drill, angkutan umum